Consequences of Longterm-Confinement and Hypobaric Hypoxia on Immunity in the Antarctic Concordia Environment - Mehta, Satish; Crucian, Brian; Sams, Clarence; Pierson, Duane; Chouker, Alexander; Stowe, Raymond; Salam, Alex (2010)
This slide presentation reviews the affects of longterm-confinement and hypobaric hypoxia on immunity in the Antarctic Concordia environment. It includes information on spaceflight-associated immune dysregulation, immune-related knowledge gaps, and ground-based space flight analogs.